2010
DOI: 10.1111/j.1440-1797.2010.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiol levels, protein carbonylation and anaerobic sulfur metabolism in erythrocytes of peritoneal dialysis and predialysis patients

Abstract: The CAPD as a replacement therapy helps to preserve thiol levels and anaerobic sulfur metabolism in erythrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Whether these observed responses are physiologically relevant depends on the endogenous concentrations of 3‐MP (in mitochondria, in whole cells or in the extracellular space). At this point, only limited data are available in this respect; some studies estimate endogenous 3‐MP concentrations in the micromolar range (47, 48).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these observed responses are physiologically relevant depends on the endogenous concentrations of 3‐MP (in mitochondria, in whole cells or in the extracellular space). At this point, only limited data are available in this respect; some studies estimate endogenous 3‐MP concentrations in the micromolar range (47, 48).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed a decreased level of sulfane sulfur in plasma of patients with a chronic kidney disease (CKD) undergoing hemodialysis (HD) (Wlodek et al, 2001), and a continuous ambulatory peritoneal dialysis (CAPD) (Wlodek et al, 2010). On the other hand, studies performed with erythrocytes of CKD patients showed a lower level of sulfane sulfur in the CKD predialysis group, while in the CAPD group the level of sulfane sulfur remained at the level observed in healthy controls (Włodek et al, 2010). This suggests that CAPD (as a replacement therapy) helps to preserve the anaerobic sulfur metabolism in erythrocytes.…”
Section: Sulfane Sulfur In the Chronic Kidney Diseasementioning
confidence: 84%
“…Moreover, the structure of Hb in ESRD patients is impaired, and these alterations are enhanced during HD [ 143 ]. Regarding RBC thiol stress in HD and PD, LMM-SH (i.e., GSH) in the RBCs of patients on continuous ambulatory PD remain at a physiological level [ 144 ], whereas the GSH level in RBCs decreases before HD, and increases after HD [ 144 , 145 ]. However, in HD patients the increase in LMM-SH level is short-lasting and limited to a brief post-HD period, while the increase in the level of LMM-SH in the RBCs of PD patients is continuous and persistent [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding RBC thiol stress in HD and PD, LMM-SH (i.e., GSH) in the RBCs of patients on continuous ambulatory PD remain at a physiological level [ 144 ], whereas the GSH level in RBCs decreases before HD, and increases after HD [ 144 , 145 ]. However, in HD patients the increase in LMM-SH level is short-lasting and limited to a brief post-HD period, while the increase in the level of LMM-SH in the RBCs of PD patients is continuous and persistent [ 144 ]. Thus, both PD and HD therapies increase the antioxidant power of RBC, but PD does so continuously, while the effect of HD is short-lasting and intermittent.…”
Section: Discussionmentioning
confidence: 99%